Understanding How Sex Influences the Impact of IL-10 on Bone Microarchitecture and Bone Metabolism Over Time. (7th June 2021) - Price, Payton; Perez, Leo; Hatter, Bethany; Robinson, Kara; Islam, Proapa; Alake, Sanmi; Ice, John; Lucas, Edralin; Smith, Brenda
Abstract: Objectives: Dietary interventions with pre- and probiotics favorably affect the gut-bone axis, mediated in part by the anti-inflammatory cytokine, interleukin (IL)-10. This study sought to understand how IL-10's impact on bone metabolism and microarchitecture differs with sex and time. Methods: Six-week-old B6.129P2- Il10 tm1Cgn /J (KO) and C57BL/6 (WT) mice were assigned in a 2 × 2 × 2 factorial design with strain (WT & KO), sex, and time (3 & 6 m) as factors. Mice were fed AIN-93G diet for 3 m followed by AIN-93 M for the study duration. Dual-energy x-ray absorptiometry was used to assess bone mineral content (BMC) and density (BMD). Micro-computed tomography was used to assess femur and lumbar vertebrae trabecular and cortical bone. Serum procollagen 1 intact N-terminal propeptide (P1NP) and C-terminal telopeptide of type I collagen (CTX-1), bone formation and resorption markers respectively, were assessed by ELISA. Data were analyzed using ANOVA; p < 0.05 was considered significant. Results: Reductions in BMC and BMD ( P < 0.05) in KO vs WT and at 3 vs 6 m were observed; a sex effect was found with reductions in BMC in KO females compared to KO males. Femoral trabecular bone volume (BV/TV) was lower ( P < 0.05) in KO vs WT, females vs males, and at 6 vs 3 m. Trabecular thickness (TbTh) decreased ( P < 0.05) in KO vs WT and increased from 3 to 6 m, while decreases in trabecular number (TbN) were greater ( P < 0.05) in KO mice, females, and at 6 m compared to counterparts. Cortical area and thickness were decreased ( P < 0.05) in KO vs WT and in females vs males, which was greater at 6 m, while cortical bone porosity was higher in KO vs WT and increased at 6 mo. Vertebral trabecular BV/TV was lower ( P < 0.05) in KO vs WT at 3 and 6 m, with KO females showing reduced BV/TV ( P < 0.05) from 3 to 6 m. Reduced TbTh and TbN were observed in KO vs WT, and females had increased ( P < 0.05) TbTh and trabecular separation and reduced TbN. P1NP showed a time effect ( P < 0.05) with reductions in WT females and males at 6 m compared to 3 m KO females ( P < 0.05). CTX-1 shows a sex effect ( P < 0.05) and a trending strain effect ( P = 0.059), with elevated serum CTX-1 in 3 m KO males compared to WT and KO females at 6 m ( P < 0.05). Conclusions: While IL-10 plays an important role in maintaining both trabecular and cortical bone, it may have a more protective effect on the cortical bone of female mice over time. Funding Sources: Oklahoma Agricultural Experiment Station.